Residential Segregation in Warsaw and its Metropolitan Area in the Context of Changing Housing Policy - Grzegorczyk, Anna; Jaczewska, Barbara (European Spatial Research and Policy, 2018)
Warsaw and its metropolitan area seem an interesting testing ground for research on the phenomenon of residential segregation in the context of the evolution of housing policy, since the city has been subject to significant changes as a result of historical events. Each of these contributed to alterations in the level and the character of residential segregation. The goal of this article is to answer the following question: Was the changing housing policy in Warsaw and the surrounding metropolitan area during the transformation period and afterwards accompanied by a modification of the segregation structure and what differences can be noticed in the whole of the metropolitan area and in the city itself?